Explosion Resistance of Three-Dimensional Mesoscopic Model of Complex Closed-Cell Aluminum Foam Sandwich Structure Based on Random Generation Algorithm - Zhen Wang; Wen Bin Gu; Xing Bo Xie; Qi Yuan; Yu Tian Chen; Tao Jiang (Complexity)
According to the randomness of the spatial distribution and shape of the internal cells of closed-cell foam aluminum and based on the Voronoi algorithm, we use ABAQUS to model the random polyhedrons of pore cells firstly. Then, the algorithm of generating aluminum foam with random pore size and random wall thickness is written by Python and Fortran, and the mesh model of random polyhedral particles and random wall thickness was established by the algorithm read in by TrueGrid software. Finally, the mesh model is impo rted into the LS-DYNA software to remove the random polyhedron part of the pore cell. Compared with the results of scanning electron microscopy and antiknock test, the morphology and properties of the model are close to those of the real aluminum foam material, and the coincidence degree is more than 91.4%. By means of numerical simulation, the mechanism of the wall deformation, destruction of closed-cell aluminum foams, and the rapid attenuation of explosion stress wave after the interference of reflection and transmission of bubbles were studied and revealed. It is found that aluminum foam deformation can be divided into four areas: collapse area, fracture area, plastic deformation area, and elastic deformation region. Therefore, the explosion resistance is directly related to the cell wall thickness and bubble size, and there is an optimal porosity rule for aluminum foam antiknock performance.